Effect of mineral salt replacement on properties of Turkish White cheese - Ecem Akan; Ozer Kinik (Mljekarstvo)
In this study, combinations of different mineral salt replacement for sodium chloride were used in Turkish White cheese production. The effect of sodium chloride substitutes on the physical, chemical and textural characteristics of cheese samples was examined. Five types of brine solution including NaCl only (K: control) (16 % w/w), only 50 % NaCl (L) (8 % w/w), 30 % CaCl2 and 70 % NaCl (M) (16 % w/w), 30% KCl and 70 % NaCl (N) (16% w/w), and PanSalt (P) (16 % w/w) were used in cheese production. PanSalt (57 % NaCl+28 % KCl+12 % MgSO4) is a commercial salt with low sodium content. The characteristics of cheeses determined within the study included the total dry matter, ash, protein, fat, salt, titratable acidity, pH values, percentage of water soluble nitrogen, percentage of trichloroacetic acid soluble nitrogen and proteose-pepton nitrogen; the sodium, calcium, potassium, phosphorus and magnesium content and the textural characteristics (via a texture profile analysis). In comparison to the control cheese, this substitution showed no significant effect on the comprehensive parameters evaluated. The Na, K, Ca and P content showed important differences among the cheese samples. The total sodium content of L, M, N and P samples decreased significantly. In regard to this research results it can be said that it is possible to produce low sodium cheese with using proper quantity of mineral salt replacers.